Concentration and association of minor and trace elements in Mukah coal from Sarawak, Malaysia, with emphasis on the potentially hazardous trace elements - Sia, Say-Gee; Abdullah, W.H. (Elsevier, 2010)
The ash yield and concentrations of twenty-four minor and trace elements, including twelve potentially hazardous trace elements were determined in Mukah coal from Sarawak, Malaysia. Comparisons made to the Clarke values show that Mukah coal is depleted in Ag, Ba, Be, Cd, Co. Mn, Ni, Se, U, and V. On the other hand, it is enriched in As, Cr, Cu, Pb, Sb, Th, and Zn. Among the trace elements studied, V and Ba are associated predominantly with the clay minerals. Manganese, Cr, Cu, Th, and Ni are mostly bound within the aluminosilicate, sulphide and/or carbonate minerals in varying proportions, though a portion of these elements are also organically bound. Arsenic, Pb and Sb are mostly organically bound, though some of these elements are also associated with the sulphide minerals. Zinc is associated with both the organic and inorganic contents of the coal. Among the potentially hazardous trace elements, Be, Cd, Co, Mn, Ni, Se, and U may be of little or no health and environmental concerns, whereas As, Cr, Pb, Sb and Th require further examination for their potential health and environmental concerns. Of particular concern are the elements As, Pb and Sb, which are mostly organically bound and hence cannot be removed by physical cleaning technologies. They escape during coal combustion, either released as vapours to the atmosphere or are adsorbed onto the fine fly ash particles. (C) 2011 Elsevier ay. All rights reserved.